Safety and immunogenicity of a pichia pastoris-expressed bivalent human papillomavirus (types 16 and 18) L1 virus-like particle vaccine in healthy Chinese women aged 9–45 years: A randomized, double-blind, placebo-controlled phase 1 clinical trial. Issue 19 (5th May 2023) - Li, Juan; Shi, Li-Wei; Yu, Bang-Wei; Huang, Li-Rong; Zhou, Ling-Yun; Shi, Li; Jiang, Zhi-Wei; Xia, Jie-Lai; Wang, Xuan-Yi; Li, Rong-Cheng; Yuan, Lin; Li, Yan-Ping; et al.
Highlights: Low or high doses of VLP HPV vaccine were well tolerated in 9–45 year-old females. Three HPV vaccinations elicited protective immune responses in 100% of vaccinees. HPV vaccination did not result in any severe or serious adverse event. Reactogenicity and immunogenicity were not affected by increasing dosage of HPV vaccine. Abstract: Background: We evaluated the safety and immunogenicity of high and low doses of a novel pichia pastoris-expressed bivalent (types 16 and 18) human papillomavirus (HPV) virus-like particle vaccine. Methods: In this randomized, double-blind, placebo-controlled phase 1 trial, we enrolled 160 healthy females aged 9–45 years in Guangxi, China who were randomized (1:1:2) to receive either low (0.5 mL) or high (1.0 mL) dosages of bivalent HPV vaccine, or placebo (aluminum adjuvant) in a 0, 2, 6 months schedule. Adverse events and other significant conditions that occurred within 30 days after each vaccination were recorded throughout the trial. Sera were collected at days 0, 60, 180 and 210 to measure anti-HPV 16/18 neutralizing antibodies. Results: A total of 160 participants received at least one dose of the HPV vaccine and 152 completed the three dose vaccination series. Reporting rates of adverse events in placebo, low dose (0.5 mL) and high dose (1.0 mL) groups were 47.5 %, 55.0 % and 55.0 %, respectively. No serious adverse events occurred during this trial. 100 % of the participants who received three doses of the HPV vaccine produced neutralizing antibodies against HPV 16/18 vaccine. For HPV 16 and HPV 18, the geometric mean titers (GMTs) were similar between the low dose group (GMTHPV 16  = 10816 [95 % CI: 7824–14953]), GMTHPV 18  = 3966 [95 % CI: 2693–5841]) and high dose group (GMT HPV 16  = 14482 [95 % CI: 10848–19333], GMT HPV 18  = 3428 [95 % CI: 2533–4639]). Conclusion: The pichia pastoris-expressed bivalent HPV vaccine was safe and immunogenic in Chinese females aged 9–45 years. The low dosage (0.5 mL) was selected for further immunogenicity and efficacy study.